The Effects of the Laurentide Ice Sheet on North American Climate during the Last Glacial Maximum - Broccoli, A.; Manabe, S. (Géographie physique et Quaternaire, 1987)
ABSTRACTA climate model, consisting of an atmospheric general circulation model coupled with a simple model of the oceanic mixed layer, is used to investigate the effects of the continental ice distribution of the last glacial maximum (LGM) on North American climate. This model has previously been used to simulate the LGM climate, producing temperature changes reasonably in agreement with paleoclimatic data. The LGM distribution of continental ice according to the maximum reconstruction of HUGHES et al. (1981) is used as input to the model. In response to the incorporation of the expanded continental ice of the LGM, the model produces major changes in the climate of North America. The ice sheet exerts an orographic effect on the tropospheric flow, resulting in a splitting of the midlatitude westerlies in all seasons but summer. Winter temperatures are greatly reduced over a wide region south of the Laurentide ice sheet, although summer cooling is less extensive. An area of reduced soil moisture develops in the interior of North America just south of the ice margin. At the same time, precipitation increases in a belt extending from the extreme southeastern portion of the ice sheet eastward into the North Atlantic. Some of these findings are similar to paleoclimatic inferences based on geological evidence.